Attitudes of secondary school students towards doing research and design activities. Issue 13 (2nd September 2018) - Vossen, T.E.; Henze, I.; Rippe, R.C.A.; Van Driel, J.H.; De Vries, M.J.
ABSTRACT: Research and design activities are often employed in STEM (Science, Technology, Engineering & Mathematics) education. This study aims to examine students' attitudes towards doing research and design activities in secondary school, among two groups of students: (1) students that take the quite recently introduced Dutch subject O&O (research & design), in which students perform authentic research and design projects related to STEM disciplines; and (2) students that do not take O&O. The subject O&O is only taught at a limited number of certified, so called 'Technasium', schools. A questionnaire, developed by the authors, was completed by 1625 students from Grades 8 and 11. Unlike previous studies on student attitudes, which usually use abstract concepts like 'science' or 'technology', the questionnaire used in this study contains active verbs to characterise research and design activities. The results showed that, in general, students who took the subject O&O had more positive attitudes towards doing research and design activities than regular students. Both student groups appeared to find doing research activities more relevant than doing design activities. The results of this study provide useful information for teachers as well as teacher educators about the existing attitudes of students, for example their preference for design projects over research projects.